THE ROLE OF THE MATRIX METALLOPROTEINASES IN THE DEVELOPMENT OF LEFT VENTRICULAR HYPERTROPHY IN PATIENTS WITH ARTERIAL HYPERTENSION AND METABOLIC SYNDROME - A. N. Zakirova; E. Z. Fatkullina; N. E. Zakirova (Столичная издательская компания, 2015)
Aim. To assess the role of the activation of matrix metalloproteinase-1 zymogen (ProMMP-1) and tissue inhibitor of metalloproteinase-1 (TIMP-1) in the development of left ventricular (LV) hypertrophy in patients with arterial hypertension (HT) and metabolic syndrome (MS) with varying degree of obesity. Material and methods. 108 patients with HT and MS divided into 3 groups according to body mass index, and 28 healthy women were studied. Intracardiac blood flow and ProMMP-1 and TIMP-1 levels were assessed. Results. Disbalance in the ProMMP-1 and TIMP-1 systems  is associated with the severity of left ventricular remodeling and grade of obesity. The changes in LV structure and geometry and activation ProMMP-1 with a deficit of TIMP-1 were most significant in patients with HT and grade 3 obesity (respectively 7.7±0.61 and 183.6±17.2 ng/ml in grade 3 obesity vs 3.5±0.3 and 291.7±22.4 ng/ml in grade 1 obesity; p<0.05). Associations between hemodynamic parameters and levels of ProMMP-1 [withLVmass index (LVMI): r=0.47; p<0.05] and TIMP-1 (with LVMI: r=-0.39;  p<0.05) were determined. Conclusion. Changes in the ProMMP-1 and TIMP-1 system in women with HT and MS are associated with the severity ofLVhypertrophy.